Si ce n'est pas de la gloire; c'est du bouillon (Itinera, 2017)
Hunger and appetite are not the same; this is perfectly demonstrated by the aesthetics and the cuisine of the Eighteenth Century. It is only hunger that subjugates the individual to disgust. Appetite refines, hunger debases. Hardly, in the Eighteenth Century, is the aesthetic fruition of disgust admitted, for it is considered as a pathological deviance. On the contrary, in the non-perverted taste, the Eighteenth Century finds a sentiment that is energy, sensory engagement, physiological tension, and imagination at the service of pleasure.Â